PP31 Data awareness for sending help (DASH): policy opportunities & challenges. Issue 1 (14th January 2019) - Drake, Archie; Pollitt, Alex; Smith, Leanne; Sklar, Elizabeth
Abstract : Background: The DASH project is a collaboration between King's College London and the London Ambulance Service (LAS). Its goal is to explore the potential impact of integrating new and emerging data sources and technologies on emergency response, using technical and policy approaches in tandem. Computer science and public health both emphasise dynamic systems thinking in which elements should be connected to others, e.g. 'data linkage', 'health in all policies'. EMS research has started to demonstrate the value of connecting LAS information systems to transport and environmental as well as emergency department data. Policy research question: what are the opportunities and challenges for EMS, wider healthcare providers and the public in the integration of new and emergent data sources and technologies in ambulance dispatch? Methods: Mixed Methods study, including literature review, framework analysis, stakeholder and process mapping, open policy development and interviews. Primary data collection (thematic analysis) entails approximately: 15 semi-structured interviews with LAS staff and 60 unstructured interviews with a variety of stakeholders. Secondary data analysis of LAS incident and response datasets over calendar year 2016 with other publicly available administrative data. Results: A wide range of new and emergent data sources have a potential impact on ambulance dispatch decision-making. The opportunities extend beyond the operational level into tactical and strategic dimensions. But the challenges are significant across a range of perspectives, impeding efforts to realise the benefits in practice. The study suggests a prioritisation of new and emergent data sources and technologies for LAS based on a utility/feasibility matrix which is presented to provoke discussion. Conclusions: More effective, dynamic 'data aware' dispatch systems are likely to improve patient outcomes. Ambulance services can usefully raise awareness to seek the necessary data and support – simultaneously furthering health system integration and wider public health goals. See https://dash.kcl.ac.uk/reports/ for project outputs.